Najarula pratibhā - Ālī, Mobāśvera, 1931- (Isalāmika Phāuṇdeśana Bāṃlādeśa era pkshe Bibhāgīẏa Isalāmī Sāṃskrtika Kendra, Khulanā Bibhāga, 1981)
Study of the literary philosophy and works of the Bengali poet Kazi Nazrul Islam, 1899-1976.